Exploring Predictors of Psychological Well-Being Among Women Living with Breast Cancer: A Cross-Sectional Study - Riska Hediya Putri; Rini Palupi; Feri Kameliawati; Salsabila Nurfadhilah Tsany (Media Publikasi Cendekia Indonesia, 2026)
Psychological well-being plays a crucial role in the recovery and quality of life of women diagnosed with breast cancer. Understanding the factors influencing well-being is essential for developing effective psychosocial interventions. This study aims to evaluate the association of several factors with the psychological well-being of women with cancer. A quantitative cross-sectional design was employed at Jenderal Ahmad Yani Regional Public Hospital, Metro, in May 2024. A total of 73 respondents were selected through convenience sampling from a population of 273 patients. Data were collected using the Multidimensional Health Locus of Control Scale (Cronbach’s α = 0.791) and Ryff’s Psychological Well-Being Scale (Cronbach’s α = 0.805). Data were analyzed using Chi-square tests and logistic regression with a significance level of p < 0.05. Chi-square analysis showed that cancer stage (p = 0.003), mastectomy status (p = 0.006), and health locus of control (p < 0.001) were significantly associated with psychological well-being. Logistic regression identified mastectomy and health locus of control as significant predictors. Women who underwent mastectomy were more likely to experience lower psychological well-being (OR = 4.34; p = 0.050), while those with a high health locus of control were more likely to report better well-being (OR = 0.021; p < 0.001). Psychological well-being in women with breast cancer is strongly influenced by health locus of control and mastectomy experience. Enhancing patients’ internal control beliefs and providing targeted psychosocial support, particularly for post-mastectomy patients, may improve psychological adaptation and overall quality of life.